View of Downtown San Jose looking North to East from City Hall - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic view of the downtown San Jose from San Jose City Hall on the Market Street Plaza. On the far left of the image, Market Street can be seen running Southeast to Northwest, past the San Jose Post Office and St. Joseph's Cathedral. On the far right of the image, San Carlos street can be seen running Southwest to Northeast, past Montgomery Hotel, the Y.W.C.A., First Baptist church, and terminating at the San Jose State Teachers College.